2018
DOI: 10.4236/cus.2018.61001
|View full text |Cite
|
Sign up to set email alerts
|

Economic Freedom, Migration and Income Change among U.S. Metropolitan Areas

Abstract: Even though metropolitan area governments have no control over state level monetary, labor, or fiscal policies, they are able to enact policies designed to enhance local living conditions-however determined. Such policies include local taxes, labor and wage policies, and regulations that can differ substantially from other metropolitan areas even within the same state. Collectively such policies create differing levels of economic freedom, as measured by standardized indices. We examine differences in levels o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Shumway (2018) and Arif et al (2020) looked at migration and economic freedom at the city level. They both found that locales with higher economic freedom experience economically and statistically significant increases in domestic in‐migration.…”
Section: Migration and Economic Freedommentioning
confidence: 99%
See 1 more Smart Citation
“…Shumway (2018) and Arif et al (2020) looked at migration and economic freedom at the city level. They both found that locales with higher economic freedom experience economically and statistically significant increases in domestic in‐migration.…”
Section: Migration and Economic Freedommentioning
confidence: 99%
“…Mulholland and Hernández-Julián (2013) report that states with higher economic freedom were attractive to migrants with secondary education and to a lesser degree those with some college. Shumway (2018) and Arif et al (2020) looked at migration and economic freedom at the city level. They both found that locales with higher economic freedom experience economically and statistically significant increases in domestic in-migration.…”
mentioning
confidence: 99%
“… 8. Examples of other work using the metropolitan statistical areas (MSA) index include Bologna, Young, and Lacombe (2016); Pavlik (2015); Koch (2015); Wong and Stansel (2016); and Shumway (2017). …”
mentioning
confidence: 99%